Contrasting long‐term records of biomass burning in wet and dry savannas of equatorial East Africa. (26th April 2014) - Colombaroli, Daniele; Ssemmanda, Immaculate; Gelorini, Vanessa; Verschuren, Dirk
Abstract Rainfall controls fire in tropical savanna ecosystems through impacting both the amount and flammability of plant biomass, and consequently, predicted changes in tropical precipitation over the next century are likely to have contrasting effects on the fire regimes of wet and dry savannas. We reconstructed the long‐term dynamics of biomass burning in equatorial East Africa, using fossil charcoal particles from two well‐dated lake‐sediment records in western Uganda and central Kenya. We compared these high‐resolution (5 years/sample) time series of biomass burning, spanning the last 3800 and 1200 years, with independent data on past hydroclimatic variability and vegetation dynamics. In western Uganda, a rapid (<100 years) and permanent increase in burning occurred around 2170 years ago, when climatic drying replaced semideciduous forest by wooded grassland. At the century time scale, biomass burning was inversely related to moisture balance for much of the next two millennia until ca. 1750 ad, when burning increased strongly despite regional climate becoming wetter. A sustained decrease in burning since the mid20th century reflects the intensified modern‐day landscape conversion into cropland and plantations. In contrast, in semiarid central Kenya, biomass burning peaked at intermediate moisture‐balance levels, whereas it was lower both during the wettest and driest multidecadal periods of the last 1200 years. Here, burning steadily increased since the mid20th century, presumably due to more frequent deliberate ignitions for bush clearing and cattle ranching. Both the observed historical trends and regional contrasts in biomass burning are consistent with spatial variability in fire regimes across the African savanna biome today. They demonstrate the strong dependence of East African fire regimes on both climatic moisture balance and vegetation, and the extent to which this dependence is now being overridden by anthropogenic activity.